The European badger (Meles meles) diet in a Mediterranean area - Ester Del Bove; Roberto Isotti (Hystrix, the Italian Journal of Mammalogy, 2001)
Abstract A study on food habits of the European badger (Meles meles) was carried out over a two year period (march 1996 - February 1998) in an area of ca 55 hectares in the Burano Lake Nature Reserve, central Italy. The badger's diet was determined by faecal analysis. The results, expressed as the frequency of occurrence, estimated volume (%) and percentage volume of each food item in the overall diet, showed that in this area the badger can be considered as a generalist, with fruit and insects as principal food items during the whole year, although some seasonal differences did occur.